Performance evaluation for SE 113 flow control system plant using self-tuning fuzzy PI controller - Janin, Zuriati; Sam, Rosidah; Masrie, Marianah; Abdul Kadir, Kushsairy; Mohamad Hanif, Noor Hazrin Hany; Gunawan, Teddy Surya (Institute of Electrical and Electronics Engineers Inc., 2019)
The aim of this project is to evaluate the dynamic process performance of SE113 Flow Control System Plant using self-tuning Fuzzy PI controller. The experimental data is used to model the process and the control analysis is done using Self-Tuning Fuzzy PI Controller. The performance evaluation is based on the percent overshoot, rise time and settling time of the process. The overall performance is compared with the conventional Proportional-Integral control method. The results had shown that self-tuning Fuzzy PI controller simplify the tediousness in tuning the controller and enhance the capability of PI controller.